Strengthening Student’s Legal Awareness through Education on the Prevention and Handling of Sexual Violence in the Basic Student Leadership Training Program - Aprillio Poppy Belladonna; Rama Adha Septiana; Yayuk Hidayah (Education of Law Journal, 2026)
Students’ legal awareness is a crucial aspect of creating a safe, inclusive, and norm-compliant university environment. One way to strengthen this legal awareness is through education on the Prevention and Handling of Sexual Violence (PPKS), integrated into the Basic Student Leadership Training (LDKM) program. This article aims to describe the implementation of PPKS education in the STKIP Pasundan LDKM program as a means of strengthening students’ legal awareness. The study employed a qualitative descriptive approach using a documentary analysis of the series of LDKM activities held on January 13–14, 2024, at Natural Hills, Lembang, West Bandung. Data were obtained from activity documents, implementation agendas, and participant briefing materials. The results of the study indicate that PPKS education was delivered in a structured manner through pre-LDKM orientation sessions as well as reinforced material at activity stations specifically addressing the Prevention and Handling of Sexual Violence in Higher Education Institutions. The integration of PPKS material with leadership education, organizational ethics, teamwork, and the reinforcement of institutional values provides students with a contextual learning experience in understanding their rights, obligations, and legal protection mechanisms on campus. This initiative not only contributes to the development of students’ leadership character but also fosters a preventive legal awareness regarding various forms of sexual violence. Thus, LDKM can serve as a strategic platform for building a campus culture that is safe, just, and centered on respect for human rights.